Philosophical-Anthropological Aspects Of Pedagogy Of Physical Efforts And Motor Activity - Вржесневський, І. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. Taking into consideration the transformations of modern society resulting from the acceleration of scientific and technological progress, the environment and a number of behavioral stereotypes inherent in our biological species are significantly changing. So, according to experts, the consequences of physical inactivity can lead to a qualitative deterioration in health. In this regard, there is a sharp concern of physicians and educators due to a sharp decrease in the physical activity of younger generations. According to the author, the growing negative trends in physical fitness and physical health of students require a separate research field in pedagogy, which would take into account the specificity of pedagogical influences on the long term physical activity and motor efforts and optimize the direction of scientific research. The aim and the tasks. The emerging trends necessitate a philosophical and anthropological understanding of the strategy of pedagogical influences in the field of physical development and physical health of younger generations, as well as a focused scientific search, the development of theoretical prerequisites and the fundamentals of updating physical education in modern and futuristic education systems. The presented work is devoted to the attempt to determine and justify the vector of such a search. Research methods. The specificity of the study involves the use of philosophical and anthropological, systemic, sociocultural approaches in the context of interdisciplinary research. Research results In the work an analysis of the place and prospects of physical education in the modern educational system and pedagogical constructs is made. In the philosophical and anthropological context, the vector of a target search for the development of physical education and the transformation of this pedagogical process into a separate pedagogical approach is presented - pedagogy of motor efforts and physical activity. The philosophical cognitive and vital premises, as well as the paradigm of the stated approach, are conceptually outlined. A new approach to the place, tasks and functions of the teacher of physical education is proposed. Furthermore, the author proposed and justified the background for the further development of the concept "The pedagogy of physical effort and physical activity". Discussion. In our opinion, modern pedagogy lacks healthy conservatism in conditions of an excess of “innovative” thoughtlessness and “innovative” shortsightedness. The desire for permanent pedagogical innovations destroys the foundations of traditional pedagogy, in turn, does not offer acceptable alternatives. And, along with this, what makes it worse is the "tunnel" vision inherent in some specialists and functionaries of the modern pedagogical community, who are "in love" with the postulates of a liberal approach to education. Conclusion. Thus, the paradigm of physical effort and physical activity pedagogy, i.e. the standard on which the theory of physical efforts and physical activity should be based is expected to be dictated by the need to maintain, the optimal balance of physical activity and physical efforts of a person as a natural basic prerequisite for maintaining basic biological (physiological and functional ) characteristics of our species and, if possible, their development in the conditions of a transforming surrounding natural, technogenic and sociocultural environment. The pedagogical process of physical education, as the anthropological constant of our education, in the future scientific research should be represented by a separate direction of pedagogy - "Pedagogy of physical effort and physical activity."